Dialectal Specifics of Onomastic Space of the Western Polissian Folklore Texts (Linguostylistic Studies, 2015)
The article highlights the issue of opposing appellatives and onyms, which is a universal feature of every language. Onyms system rootedness into the dialect environment definitely actualizes accurate reading of folklore texts aimed at revealing in them the dialectal features at different linguistic levels. The article deals with the detailed analysis of dialectal specificity of onyms as structural elements of folk language at the phonetic, morphological and derivational levels. The analysis has been focused on the materials of epic oral poetic texts of Western Polissia and modern dialectological data. It has been revealed that proper names fixed in western Polissian folk texts retain the language features of the locality where they are prevalent. The key findings of the research provide grounds to draw the conclusion that the variability of proprial lexica at dialect level is closely connected with the specifics of reflexation of the old vowels, the emergence of prothetic and epenthetic sounds, dissimilative processes, peculiarities of noun forms formation, derivational potential of western Polissian patois and other factors. The conclusion is confirmed by the presence of the appropriate appellative forms in the coherent speech of Polishchuks reproduced graphically in the texts compiled by H. L. Arkushyn in his collections. Key words: dialects, onyms, names options, folklore texts, Western Polissia. References